Effects of recreational and residential functional land use on urban soils - Gordienko, Oleg; Kulik, Anastasia (Hungarian Geographical Bulletin, 2024)
Soils in residential areas of cities are heavily degraded, and the environmentally protective and formative functions are instead realized by the soils in recreational areas (city parks, etc.). The study aimed to analyse the influence of functional land use and the level of anthropogenic impact on the properties of anthropogenic horizons (Au and Aτ) in the city of Volgograd, Russia. In this study, we analysed 50 soil samples from the city’s recreational and residential functional areas under field and laboratory conditions. The study evaluated the morphological aspects (thickness, colour, structure, and presence of artefacts), physical properties (bulk density, texture), and chemical properties (pHwater, salt content, CaCO3, Corg, SOCstoc)of the soils. The anthropogenic Au horizons in residential areas exhibited a clumpy structure, numerous artefacts, and significant compaction. Conversely, the soils in recreational zones contained fewer anthropogenic artefacts, with the Aτ horizons characterized by a lumpy structure. The anthropogenic horizons’ median and mean property values in the functional zones showed significant differences. The acid-alkaline properties of the studied horizons were weakly alkaline in recreational areas and alkaline in residential areas. A common feature of all anthropogenic horizons was the variability in chemical, physical, and morphological properties depending on the functional zone and level of anthropogenic load. The indicators of a specific level of anthropogenic impact on urban landscapes included horizon thickness, Corg content, colour, and structure.